2016
DOI: 10.21082/ijas.v9n1.2008.p24-28
|View full text |Cite
|
Sign up to set email alerts
|

VARIABILITY AND CORRELATION OF AGRONOMIC CHARACTERS OF MUNGBEAN GERMPLASM AND THEIR UTILIZATION FOR VARIETY IMPROVEMENT PROGRAM Lukman Hakim

Abstract: Information on the variability and correlation between agronomic characters of mungbean accessions with their yield are important for supporting breeding program of the plant. A total of 350 mungbean accessions were evaluated at Muara Experimental Farm, Indonesian Center for Food Crops Research and Development, Bogor, during the dry season of 2005. The experiment was conducted in a completely randomized block design with three replications. Each accession was planted in two rows of 5 m long. Plant spacing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
5
5
0
Order By: Relevance
“…This indicates that there was a strong inherent association between them and the genotypic expression of correlation was less influenced by environmental factors. This result confirms the earlier findings of Hakim et al [2008].…”
Section: Correlation Co-efficientsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that there was a strong inherent association between them and the genotypic expression of correlation was less influenced by environmental factors. This result confirms the earlier findings of Hakim et al [2008].…”
Section: Correlation Co-efficientsupporting
confidence: 93%
“…Days to 50 % flowering had nonsignificant positive correlation with grain yield per plant at genotypic level, indicated that early flowering genotypes are desirable for grain yield per plant( Table 1). These results confirm the earlier finding of Hakim (2008). The days to 50 % flowering was positively and significantly correlated with days to maturity, indicated the direct relationship between them and improvement in both the traits as well as yield could be achieved by exercising selection for either of the trait.…”
Section: A Genotypic Correlations Co-efficientssupporting
confidence: 91%
“…All other traits recorded minimum direct effect on seed yield / plant. Present result is in accordance with findings of Hakim (2016). These results clearly showed that major importance needed to be given for number of pods / plant for the improvement of greengram through interspecific hybridization.…”
Section: Path Coefficient Analysissupporting
confidence: 92%
“…Soweon and Seonam produced 2.58 and 2.2 Mg ha −1 , respectively. Dawon had the lowest grain yield (1.55 Mg ha −1 ), which might be associated with its higher lodging rate [33], small plant height [34,35], lower number of pods per plant [35,36], and small seed size [36]. In addition, Dawon had the lowest GDDs from sowing to flowering (Table 4), which might be associated with its lower yield.…”
Section: Estimations Of Lodging Height and Grain Yield For All Six Soybean Cultivarsmentioning
confidence: 99%